A Novel Approach for the Assessment of the Nocturnal Image of the Cultural Landscape. Issue 1 (2nd January 2023) - Valetti, Lodovica; Pellerey, Franco; Pellegrino, Anna
ABSTRACT: Policies aimed at urban and territorial development stressed the importance of landscape as a significant resource for sustainable and economic development. In this perspective, research on landscape visual values and people preferences can support the enhancement of the global values of territories. Currently, the theoretical framework and approaches are mainly limited to the day images of sites, while nighttime landscape is not usually considered. In this study, we defined a methodological approach to address the analysis of the nocturnal image of cultural landscape contexts, in order to define indications and support the inclusion of visual values in the process of public lighting design. The approach was conceived for territorial contexts characterized by the presence of small urban settlements located in prominent positions and involved a subjective survey, an in-field measurement campaign, and statistical analysis to identify significant correlations between subjective judgments and quantitative parameters. The effectiveness of the approach was assessed through the application to a case study. The study allowed identifying subjective factors (overall impact, architecture and historicity, correspondence, alteration) and objective parameters (ratios of regions' area, luminance values, and luminance contrasts) which describe the nightscape of cultural landscape. Results demonstrated the presence of significant correlation between subjective factors and objective parameters. The application of the method could provide designers and planners indications useful for the design of outdoor lighting system, in order to include perceptual aspects in a holistic design approach, which promotes environmental, energy, economic, and cultural sustainability.